Abdominal imaging : computational and clinical applications : 6th International Workshop, ABDI 2014, held in conjunction with MICCAI 2014, Cambridge, MA, USA, September 14, 2014 - Yoshida, Hiroyuki 1947-; Näppi, Janne J.; Saini, Sanjay (Lecture notes in computer science, 2014)
This book constitutes the refereed proceedings of the 6th International Workshop ABDI 2014, held in conjunction with MICCAI 2014, in Cambridge, MA, USA, in September 2014. The book includes 29 papers which were carefully reviewed and selected from 33 submissions. The topics covered are liver and pancreas - ablation, perfusion, and segmentation; gastrointestinal tract - Crohn's disease; gastrointestinal tract - colonoscopy, colonography; and abdominal operation planning - registration, segmentation.